Amelioration of Behavioral and Cognitive Impairment of Ethanolic Leaf Extract of Ziziphus Talanai Against MSG in Mice - Glen Nolasco; Graciela Ann Escoto; Lourdes Fatima David; Aaron Carl te; Frienchie Ann Yamauchi (Journal of Healthcare and Biomedical Science, 2023)
Ziziphus talanai is an endemic plant species in the Philippines. Recently, this plant's phytochemical analysis revealed pivotal compounds with different pharmaceutical properties, including the neuroprotective activity in the mice cerebellum. Nonetheless, the scarcity of information on the neuroprotective potential of this plant has been a focal point. Thus, this study aimed to evaluate the neuroprotective potential of Z. talanai extract against MSG-induced aberrations in mice. A total of 24 mice were distributed and administered 9000mg/kg of MSG (T-), MSG and 1000mg/kg of L-taurine (T+), 100% of extract (T1), MSG, and 25% extract (T2), MSG and 50% of the extract, MSG and 75% extract, and MSG and 100% of the extract. The results of the test crawling along the rope showed that mice treated with MSG exhibited anxiety-like behavior, while mice treated with L-taurine managed to surpass the atrocious effect of MSG. In mice treated with the extracts, it is revealed that there is anxiolytic effect that has direct relation between the concentration and results. The results of the Y-maze test obtained significant differences between the MSG-treated group versus extract alone, L-taurine, 50%, 75%, and 100% extract. Interestingly, a 75% concentration of the plant extract was the most promising of the group results. These justify the ameliorative potential of Z. talanai extract on the behavior deficits and cognitive impairment of mice treated with MSG.